Direct Calculation of Permeability by High-Accurate Finite Difference and Numerical Integration Methods (Communications in Computational Physics, 2018)
Velocity of fluid flow in underground porous media is 6∼12 orders of magnitudeslower than that in pipelines. If numerical errors are not carefully controlled inthis kind of simulations, high distortion of the final results may occur [1–4]. To fit thehigh accuracy demands of fluid flow simulations in porous media, traditional finitedifference methods and numerical integration methods are discussed and correspondinghigh-accurate methods are developed. When applied to the direct calculationof full-tensor permeability for underground flow, the high-accurate finite differencemethod is confirmed to have numerical error as low as 10−5% while the high-accuratenumerical integration method has numerical error around 0%. Thus, the approachcombining the high-accurate finite difference and numerical integration methods is areliable way to efficiently determine the characteristics of general full-tensor permeabilitysuch as maximum and minimum permeability components, principal directionand anisotropic ratio.